A critical assessment on evaporative cooling performance of micro finned micro gap for high heat flux applications - Ahmed, Shugata; Ismail, Ahmad Faris; Sulaeman, Erwin; Muhammad, Hasibul Hasan (Asian Research Publishing Network (ARPN), 2016)
Micro gap heat sinks reduce flow boiling instabilities and generate more uniform surface temperature than typical microchannels. Heat transfer rate in micro gaps can be increased by providing micro fins. Micro fins increase surface area as well as generate turbulence, which disturbs the laminar sub-layer. Hence, heat transfer rate enhances due to rapid fluid mixing. In this paper, effectiveness of flow boiling in a micro finned micro gap for cooling purpose has been investigated numerically. Flow boiling of pure water in the heat sink has been simulated using FLUENT 14.5 release. From results, it has been observed that upper and lower solid-fluid interfaces show different thermal behaviors with heat flux increment.Area-weighted average heat transfer coefficient of upper surface increases with increasing heat flux, while decreases for lower surface. In a net effect, thermal resistance of the heat sink increases with heat flux increment after onset of boiling for low Reynolds number. However, for high Reynolds number, thermal resistance changes slowly with heat flux variation. Pressure drop penalty has been found high for high heat fluxes during boiling. Interestingly, increment of pumping power is not always cost effective as thermal resistance does not decrease sharply all over the range. Hence, it is suggested that optimized pumping power should be used for highest efficiency.